Morphologic Anomalies of Upper Cervical Vertebrae in Swedish Children Born with Nonsyndromic Cleft Lip and/or Palate Compared to Swedish Children without Cleft. (July 2019) - Karsten, Agneta; Sideri, Metaxia; Spyropoulos, Meropi
Objective: To examine and compare the prevalence of morphologic anomalies of the upper cervical vertebrae in Swedish children with nonsyndromic cleft lip and/or palate to Swedish children without cleft. Design: Retrospective study on lateral cephalograms. Setting: Division of Orthodontics, Department of Dental Medicine, Karolinska Institutet, Stockholm, Sweden. Patients: The cleft group consisted of 325 children (150 girls and 175 boys) born with nonsyndromic cleft lip and/or palate (mean age: 11.1 years). The control group consisted of 325 children without cleft, matched for age and gender. Main Outcome Measures: Lateral cephalograms exposing upper cervical vertebrae (C1-C3) were examined regarding morphologic anomalies such as posterior arch deficiencies, fusion of vertebrae, odontoid anomalies, and deviations of the vertebral artery canal. Results: The prevalence of children with morphologic anomalies of the upper cervical vertebrae was 24.3% (n = 79) in children with cleft and 12.6% (n = 41) in children without cleft. Posterior arch deficiency and vertebral fusion were significantly more frequent in children with cleft ( P < .001). No statistically significant differences were found between the 2 groups regarding odontoid and vertebral artery canal anomalies. Conclusions: Morphologic anomalies of the upper cervical vertebrae in Swedish children with nonsyndromic cleft lip and/or palate were significantly more frequent compared to similar anomalies in Swedish children without cleft.